The Axiology of Islamic Education in the Habitual Literacy of Qur’anic Reading at SMP Nurul HAQ Klaten - Mujiburrohman Mujiburrohman; Putri Firdaus Fahmi (Jurnal Ilmiah Guru Madrasah, 2025)
This study focuses on the habitual literacy of Qur’anic reading at SMP Nurul Haq Klaten, aiming to understand the role of teachers, the impact on students’ character, and the challenges of implementation from the perspective of Islamic educational axiology. The research questions include: (1) how teachers guide Qur’anic literacy in full-day and boarding school settings; (2) the impact of literacy habits on students’ character and behavior; and (3) the challenges that arise and strategies employed to overcome them.This study uses a qualitative descriptive approach with a case study design. Informants were selected purposively, including the principal, Islamic Religious Education teachers, Qur’anic literacy facilitators, and students. Data were collected through observations, semi-structured interviews, and documentation studies, and analyzed interactively through data reduction, presentation, and conclusion drawing, with triangulation applied to ensure data validity.The results indicate that Qur’anic literacy habits are conducted intensively through halaqah sessions and integrated with both formal and non-formal activities, significantly shaping students’ religious character and enhancing discipline, responsibility, honesty, and social awareness. Teachers play a crucial role as facilitators, motivators, and role models. Challenges such as differences in students’ reading abilities, time management, and curriculum limitations can be addressed through adaptive strategies and the integration of non-formal activities.This study confirms that Qur’anic literacy serves as an effective means to internalize the values of Islamic educational axiology and provides an empirical foundation for developing literacy practices in other Islamic schools.